Strength of 3Y-TZP and feldspathic porcelain subjected to different cooling methods - Almeida-júnior, Antonio Alves De; Longhini, Diogo; Galvão, Beatriz Regalado; Santos, Claudinei Dos; Adabo, Gelson Luis (Faculdade de Odontologia de Piracicaba - UNICAMP, 2014)
AIM: To investigate the effect of the cooling rate on flexural strength of monolayer and bilayer porcelain/zirconia (Y-TZP) bars. METHODS: Forty-five specimens were made for each design group: (PM) monolithic specimens of veneer porcelain Vita VM9 (Vita, Germany); (ZM) monolithic specimens of zirconia (ZiHP; ProtMat, Brazil); (PB) bilayer specimens zirconia/porcelain with porcelain on lower surface; and (ZB) bilayer specimens porcelain/zirconia with zirconia on lower surface. Each group was cooled by three different methods after porcelain sintering: slow specimens were cooled inside the turned-off furnace; normal specimens were removed from the furnace and cooled in air at room temperature; and fast specimens were removed from the furnace at 910°C and cooled by compressed air for 10 s. Specimens were polished and flexural strength was measured in water at 37 °C (n=15). Maximum load at fracture was recorded, and equations for simple (monolayer) and composite (bilayer) structures were used to calculate the flexural strength. RESULTS were analyzed using one-way ANOVA (p<0.05) and Tukey test separately for each design. RESULTS: The results of one-way ANOVA were statistically significant only for the PB group. The post-hoc Tukey test showed the highest flexural strength for fast cooling and the lowest for slow cooling; the normal cooling was statistically similar to both. CONCLUSIONS: Cooling methods affected only the flexural strength of bilayer specimens with porcelain on low surface (under tension) when the slow cooling method was used.
Keywords: dental porcelain; zirconium; material resistance